MEMBANGUN UMKM BERBASIS WAKAF PRODUKTIF : PENDEKATAN HUKUM BISNIS ISLAM TERHADAP PEMBIAYAAN ALTERNATIF - Ganesta Putrya Awara; Muhammad Fadli Ikhwan; Sandria Zhafrani (Taksasila Edukasi Insani, 2025)
This study examines the potential of productive waqf as an alternative financing mechanism for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia within the framework of Islamic business law. Amid limited access to conventional financing due to administrative and interest-based barriers, productive waqf emerges as a sharia-compliant and socially inclusive solution. Using a qualitative-descriptive method through library research, the study analyzes literature from academic sources and waqf institutions. The findings show that productive waqf not only offers capital assistance but also empowers MSMEs through training, infrastructure, and fair financing schemes. This financing model aligns with Islamic principles such as justice, prohibition of riba and gharar, and public benefit (maslahah). Successful implementations by institutions like Dompet Dhuafa and Bank Wakaf Mikro demonstrate its effectiveness in increasing business capacity, income, and job creation. The study concludes that productive waqf can significantly contribute to sustainable and equitable economic development when supported by strong regulation, professional nazhir management, and broader public awareness.Keywords: Islamic business law, MSMEs, productive waqf, alternative financing, sharia economy